Nanoneedle-like zinc oxide as a filler particle for an experimental adhesive resin - Vicente Castelo Branco Leitune; Priscila Raquel Schiroky; Bruna Genari; Melissa Camassola; Felipe Antonio Lucca S; Susana Maria Werner Samuel; Fabrício Mezzomo Collares (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to develop an experimental adhesive resin with nanoneedle-like zinc oxide (N-ZnO), an inorganic filler, that could avoid particle agglomeration and lead to a homogeneous stress distribution within the material and characterize it. Materials and Methods: N-ZnO particles obtained by a thermal evaporation technique were characterized regarding size and surface area and added at 0 (control), 1, 2, 5, and 10 wt%, to an experimental adhesive resin. The following experimental adhesive resins' properties were assessed: radiopacity, contact angle to conditioned enamel and dentin, color, degree of conversion, flexural strength, resistance to degradation, and cytotoxicity. Statistical analysis was performed using one-way ANOVA and Tukey's post hoc test and paired Student's t-test. Results: Particles presented a mean particle size of 40 nm and a specific surface area of 16 m2/g. N-ZnO10%showed an increased radiopacity when compared to N-ZnO0%. Contact angles were significantly higher for N-ZnO10%at enamel and N-ZnO2%, N-ZnO5%, and N-ZnO10%at dentin. All groups showed color change when compared to N-ZnO0%. Higher the N-ZnO concentration, lower the degree of conversion. There were no significant differences between the groups for flexural strength and resistance to degradation. The addition of N-ZnO showed no difference in cytotoxicity when compared to positive control, N-ZnO0%, and all groups showed higher values than negative control. Conclusions: N-ZnO possibly exceeded potential limitations due to particles' agglomeration and improved the transference and distribution of stress within the material. It could be effectively used as a filler for adhesive resins.